2013
DOI: 10.1177/0956462413482814
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis in HIV patients: a case–control study

Abstract: This study investigates the association of avascular necrosis (AVN) in human immunodeficiency virus (HIV)-positive individuals with possible risk factors, including antiretroviral therapy. Clinic records of all AVN cases diagnosed up to July 2009 in HIV-positive patients attending North Middlesex Hospital, London, UK were retrospectively reviewed. For each case, one control was randomly selected, matched for gender, age, nadir CD4 count and date of HIV diagnosis. Of 15 symptomatic AVN cases identified, eight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
6
1
1
Order By: Relevance
“…This hypothesis was supported by a univariable association of AVN with a CD4 nadir >200 cells/µL and corticosteroid use >3 months. Prolonged corticosteroid treatment is more often used in late presenters (eg, as adjunctive treatment to opportunistic infections) or subsequent to ART start (eg, management of immune reconstitution inflammatory syndrome) [5, 6, 10, 12, 20, 21]. In contrast to other studies, we did not observe an association with the use of testosterone or megestrol acetate.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was supported by a univariable association of AVN with a CD4 nadir >200 cells/µL and corticosteroid use >3 months. Prolonged corticosteroid treatment is more often used in late presenters (eg, as adjunctive treatment to opportunistic infections) or subsequent to ART start (eg, management of immune reconstitution inflammatory syndrome) [5, 6, 10, 12, 20, 21]. In contrast to other studies, we did not observe an association with the use of testosterone or megestrol acetate.…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, we confirm previously recorded AVN risk factors such as heterosexual HIV acquisition, moderate/severe alcohol consumption [10, 21], hyperlipidemia, and corticosteroid use >3 months (trend) [5, 8, 10, 12, 21]. Our observation that TDF contributes to AVN is potentially worrisome and needs to be confirmed in other patient populations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Many studies [29][30][31] have shown an association of ON in HIVpositive individuals undergoing antiretroviral therapy. It is unknown whether or not the association is due to protease inhibitors alone or is multifactorial in combination with other risk factors such as the HIV infection itself, a history of systemic corticosteroid use, or hyperlipidemia [32][33][34][35].…”
Section: Othersmentioning
confidence: 99%
“…Unlike the West, where they appear as frequently associated with HIV and its treatment [22][23][24][25][26], no case of connectivity and vasculitis was found in our study.The rarity of these affections in the black race would be the main reason. The osteonecrosis are therefore now associated with HIV and/or with its treatment [9,[27][28][29] and they tend to be bilateral in our study. Tendinopathies and carpal tunnel syndrome are also common during HIV infection [10][11][12]30].…”
Section: Discussionmentioning
confidence: 84%